HARTA BERSAMA DALAM PERKAWINAN DI INDONESIA (MENURUT PERSPEKTIF HUKUM ISLAM) - RAHMANIAH, AMELIA (Syariah: Jurnal Hukum dan Pemikiran, 2015)
Joint property in marriage law in Indonesia comes from Indonesian tradition law which isthen used as the written law namely Undang-Undang No. 1 Tahun 1974 About Marriage and Compila-tion of Islamic Law with the aim to provide balanced position between husband and wife. The objectiveis in line with maqashid al shariah. But, the joint property that occur automatically in the written lawneeds to be reconstructed based on the ownership of Islamic law that the existence of joint property isin line with Islamic law.